Memorial Tributes: Volume 18 - National Academy of Engineering (The National Academies Press, 2014)
This is the 18th Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964. Under the charter of the National Academy of Sciences, the National Academy of Engineering was formed as a parallel organization of outstanding engineers. Members are elected on the basis of significant contributions to engineering theory and practice and to the literature of engineering or on the basis of demonstrated unusual accomplishments in the pioneering of new and developing fields of technology. The National Academies share a responsibility to advise the federal government on matters of science and technology. The expertise and credibility that the National Academy of Engineering brings to that task stem directly from the abilities, interests, and achievements of our members and foreign associates, our colleagues and friends, whose special gifts we remember in this book.
Keywords: Biography and Autobiography

Limited Affordable Low-Volume Manufacturing: Summary of a Workshop - National Research Council (The National Academies Press, 2014)
Limited Affordable Low-Volume Manufacturing is the summary of a workshop convened by the National Materials and Manufacturing Board of the National Research Council in August 2013 to discuss affordable, low-volume manufacturing. The workshop focused on four critical issues relevant to manufacturing: low-volume manufacturing; use of commercial off-the-shelf equipment; short production runs; and commercial manufacturing services. The workshop discussion also considered variable-rate manufacturing and high-mix manufacturing, both aspects of low-volume manufacturing. This report examines the characteristics of low-volume manufacturing and considers future advances in limited affordable low-volume manufacturing in the United States.
Keywords: Industry and Labor

3D Printing in Space - National Research Council (The National Academies Press, 2014)
Additive manufacturing has the potential to positively affect human spaceflight operations by enabling the in-orbit manufacture of replacement parts and tools, which could reduce existing logistics requirements for the International Space Station and future long-duration human space missions. The benefits of in-space additive manufacturing for robotic spacecraft are far less clear, although this rapidly advancing technology can also potentially enable space-based construction of large structures and, perhaps someday, substantially in the future, entire spacecraft. Additive manufacturing can also help to reimagine a new space architecture that is not constrained by the design and manufacturing confines of gravity, current manufacturing processes, and launch-related structural stresses. The specific benefits and potential scope of additive manufacturing remain undetermined. The realities of what can be accomplished today, using this technology on the ground, demonstrate the substantial gaps between the vision for additive manufacturing in space and the limitations of the technology and the progress that has to be made to develop it for space use. 3D Printing in Space evaluates the prospects of in-space additive manufacturing. This report examines the various technologies available and currently in development, and considers the possible impacts for crewed space operations and robotic spacecraft operations. Ground-based additive manufacturing is being rapidly developed by industry, and 3D Printing in Space discusses government-industry investments in technology development. According to this report, the International Space Station provides an excellent opportunity for both civilian and military research on additive manufacturing technology. Additive manufacturing presents potential opportunities, both as a tool in a broad toolkit of options for space-based activities and as a potential paradigm-changing approach to designing hardware for in-space activities. This report makes recommendations for future research, suggests objectives for an additive manufacturing roadmap, and envisions opportunities for cooperation and joint development.
Keywords: Space and Aeronautics; Engineering and Technology

Big Data in Materials Research and Development: Summary of a Workshop - National Research Council (The National Academies Press, 2014)
Big Data in Materials Research and Development is the summary of a workshop convened by the National Research Council Standing Committee on Defense Materials Manufacturing and Infrastructure in February 2014 to discuss the impact of big data on materials and manufacturing. The materials science community would benefit from appropriate access to data and metadata for materials development, processing, application development, and application life cycles. Currently, that access does not appear to be sufficiently widespread, and many workshop participants captured the constraints and identified potential improvements to enable broader access to materials and manufacturing data and metadata. This report discusses issues in defense materials, manufacturing and infrastructure, including data ownership and access; collaboration and exploitation of big data's capabilities; and maintenance of data.
Keywords: Engineering and Technology

Development Planning: A Strategic Approach to Future Air Force Capabilities - National Research Council (The National Academies Press, 2014)
The development and application of technology has been an essential part of U.S. airpower, leading to a century of air supremacy. But that developmental path has rarely been straight, and it has never been smooth. Only the extraordinary efforts of exceptional leadership - in the Air Forces and the wider Department of Defense, in science and in industry - have made the triumphs of military airpower possible. Development Planning provides recommendations to improve development planning for near-term acquisition projects, concepts not quite ready for acquisition, corporate strategic plans, and training of acquisition personnel. This report reviews past uses of development planning by the Air Force, and offers an organizational construct that will help the Air Force across its core functions. Developmental planning, used properly by experienced practitioners, can provide the Air Force leadership with a tool to answer the critical question, Over the next 20 years in 5-year increments, what capability gaps will the Air Force have that must be filled? Development planning will also provide for development of the workforce skills needed to think strategically and to defectively define and close the capability gap. This report describes what development planning could be and should be for the Air Force.
Keywords: Conflict and Security Issues

2013-2014 Assessment of the Army Research Laboratory: Interim Report - National Research Council (The National Academies Press, 2014)
The National Research Council's Army Research Laboratory Technical Assessment Board provides biennial assessments of the scientific and technical quality of the research, development, and analysis programs at the Army Research Laboratory, focusing on ballistics sciences, human sciences, information sciences, materials sciences, and mechanical sciences. This interim report summarizes the findings of the Board for the first year of this biennial assessment. During the first year the Board examined the following elements: within ballistic sciences, terminal ballistics; within human sciences, translational neuroscience and soldier simulation and training technology; within information sciences, autonomous systems; and within materials sciences, energy materials and devices, photonic materials and devices, and biomaterials. The review of autonomous systems included examination of the mechanical sciences competency area for autonomous systems. A second, final report will subsume the findings of this interim report and add the findings from the second year of the review, during which the Board will examine additional elements.
Keywords: Conflict and Security Issues

Furthering America's Research Enterprise - National Research Council (The National Academies Press, 2014)
Scientific research has enabled America to remain at the forefront of global competition for commercially viable technologies and other innovations. For more than 65 years, the United States has led the world in science and technology. Discoveries from scientific research have extended our understanding of the physical and natural world, the cosmos, society, and of humans - their minds, bodies, and economic and other social interactions. Through these discoveries, science has enabled longer and healthier lives, provided for a better-educated citizenry, enhanced the national economy, and strengthened America's position in the global economy. At a time of budget stringency, how can we foster scientific innovation to ensure America's unprecedented prosperity, security, and quality of life? Although many studies have investigated the impacts of research on society, Furthering America's Research Enterprise brings to bear a fresh approach informed by a more holistic understanding of the research enterprise as a complex, dynamic system. This understanding illuminates why America's research enterprise has historically been so successful; where attention should be focused to increase the societal benefits of research investments; and how those who make decisions on the allocation of funds for scientific research can best carry out their task. This report will be of special interest to policy makers who support or manage the research enterprise, to others in public and private institutions who fund research, to scholars of the research enterprise, and to scientists and engineers who seek to better understand the many pathways through which their research benefits society.
Keywords: Policy for Science and Technology

Estimating the Economic Impact of Air Cargo Operations at Airports, Part 1: User’s Guidebook and Part 2: Research Report - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Airport Cooperative Research Program (ACRP) Web-Only Document 20: Estimating the Economic Impact of Air Cargo Operations at Airports, Part 1: User’s Guidebook and Part 2: Research Report provides guidance and tools to practitioners who estimate the economic value of air cargo facilities and operations to their communities and regions.
Keywords: Transportation and Infrastructure

SBIR at the Department of Defense - National Research Council (The National Academies Press, 2014)
Created in 1982 through the Small Business Innovation Development Act, the Small Business Innovation Research (SBIR) program remains the nation's single largest innovation program for small business. The SBIR program offers competitive awards to support the development and commercialization of innovative technologies by small private-sector businesses. At the same time, the program provides government agencies with technical and scientific solutions that address their different missions. SBIR at the Department of Defense considers ways that the Department of Defense SBIR program could work better in addressing the congressional objectives for the SBIR program to stimulate technological innovation, use small businesses to meet federal research and development (R & D) needs, foster and encourage the participation of socially and economically disadvantaged small businesses, and increase the private sector commercialization of innovations derived from federal R&D. An earlier report, An Assessment of the Small Business Innovation Research Program at the Department of Defense, studied how the SBIR program has stimulated technological innovation and used small businesses to meet federal research and development needs. This report builds on the previous one, with a revised survey of SBIR companies. SBIR at the Department of Defense revisits some case studies from the 2009 study and develops new ones, and interviews agency managers and other stakeholders to provide a second snapshot of the program's progress toward achieving its legislative goals.
Keywords: Industry and Labor

The Flexible Electronics Opportunity - National Research Council (The National Academies Press, 2014)
Flexible electronics describes circuits that can bend and stretch, enabling significant versatility in applications and the prospect of low-cost manufacturing processes. They represent an important technological advance, in terms of their performance characteristics and potential range of applications, ranging from medical care, packaging, lighting and signage, consumer electronics and alternative energy (especially solar energy.) What these technologies have in common is a dependence on efficient manufacturing that currently requires improved technology, processes, tooling, and materials, as well as ongoing research. Seeking to capture the global market opportunity in flexible electronics, major U.S. competitors have initiated dedicated programs that are large in scope and supported with significant government funding to develop and acquire these new technologies, refine them, and ultimately manufacture them within their national borders. These national and regional investments are significantly larger than U.S. investment and more weighted toward later stage applied research and development. The Flexible Electronics Opportunity examines and compares selected innovation programs both foreign and domestic, and their potential to advance the production of flexible electronics technology in the United States. This report reviews the goals, concept, structure, operation, funding levels, and evaluation of foreign programs similar to major U.S. programs, e.g., innovation awards, S&T parks, and consortia. The report describes the transition of flexible electronics research into products and to makes recommendations to improve and to develop U.S. programs. Through an examination of the role of research consortia around the world to advance flexible electronics technology, the report makes recommendations for steps that the U.S. might consider to develop a robust industry in the United States. Significant U.S. expansion in the market for flexible electronics technologies is not likely to occur in the absence of mechanisms to address investment risks, the sharing of intellectual property, and the diverse technology requirements associated with developing and manufacturing flexible electronics technologies. The Flexible Electronics Opportunity makes recommendations for collaboration among industry, universities, and government to achieve the critical levels of investment and the acceleration of new technology development that are needed to catalyze a vibrant flexible electronics industry.
Keywords: Engineering and Technology